2013
DOI: 10.1159/000355538
|View full text |Cite
|
Sign up to set email alerts
|

High Latency of Tuberculosis Manifestation in a Premature Extremely Low Birth Weight Infant with Favorable Outcome

Abstract: We report a case of possible congenital tuberculosis in a 22+2 weeks, 460 g, vaginally delivered female infant born to a mother suffering from tuberculous endometritis, diagnosed soon after delivery. At 156 days of age, Mycobacterium tuberculosis was detected via PCR from the infant's gastric juice and was subsequently isolated. There was no evidence for horizontal transmission. Mother and child were treated successfully. This case illustrates the possibility of significant latency between infection and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Cantwell et al [5] reported that the average age at the onset of congenital tuberculosis was 24 days (range, 1–84 days). Vogel et al [10] reported that some patients with congenital tuberculosis did not develop symptoms until 3 months after birth or longer. The longest duration between birth and the onset of symptoms was 154 days.…”
Section: Discussionmentioning
confidence: 99%
“…Cantwell et al [5] reported that the average age at the onset of congenital tuberculosis was 24 days (range, 1–84 days). Vogel et al [10] reported that some patients with congenital tuberculosis did not develop symptoms until 3 months after birth or longer. The longest duration between birth and the onset of symptoms was 154 days.…”
Section: Discussionmentioning
confidence: 99%
“…Both mother and child were treated favorably. This case report highlighted a prolonged latency period of TB infection, emphasizing the need for urgent treatment of neonates in such situations [21], especially taking into account pediatric acute respiratory failure [22].…”
Section: Discussionmentioning
confidence: 91%
“…As said in literature, symptoms appear only in newborns after third week of life, with a median age of 28 days [5]. On the other hand, there have been cases of late onset up to 3 months of life or over, as the case study by Vogel et al has shown [34], describing the appearance of congenital TB manifestation at 154 days after birth. And another study reported the case on day 112 [37].…”
Section: Discussionmentioning
confidence: 99%